Tea Growing and Socio-Economic Development of Small Holder Farmers: A Case Study of Rushoroza Kabale District. - Byamukama, Hillary (Kabale University, 2025)
The study focused on the assessment of tea growing and socio-economic development of smallholder farmers: a case study of Rushoroza Kabale district. The objectives of the study were to find out the contributions of tea growing to the socio-economic development of farmers, to identify challenges faced by tea farmers towards socio-economic development, and to suggest possible strategies to the challenges faced by tea farmers socio-economic development, was a critical review of tea growing on socio-economic development and studied both theoretically and empirically in the existing literature on tea growing as an independent variable and socio-economic development as the dependent variable. The research used descriptive research design and methods of data collection which were both questionnaires and interview guide. The research used both qualitative and quantitative methods of data collection and analysis. The research used a sample size of 57 respondents and the sampling techniques were based on simple random which was used in collecting data from respondents. Purposive sampling was also used to collect data from respondents who participated in the study. The study findings indicated that there were contributions of tea growing to welfare they included; poverty alleviation, food security, illiteracy level, financial support, capital base, collateral security, and illiteracy level. However, the majority of the respondents revealed that collateral security 28% was the major factor in credit access by tea farmers. Findings on challenges include; lack of capital, bilateral relationships, poor provision of incentives, lack of agricultural inputs, improper welfare scheme, and NGO involvement. The majority of the respondents revealed that the major challenge was the lack of access to capital with 20%. Strategies to mitigate the challenges faced by farmers include; sensitization of farmers, training, leadership skills, basic planning skills, accountability, financial support, and government concern. The majority of the respondents revealed a government concern with 25% was one of the best applicable strategies to mitigate the challenges faced by tea farmers on welfare in the Kitumba sub-county Kabale district. The recommendations for the study include there need for the involvement of extension workers in decision-making and consultation on policies regarding agricultural and rural development and their ability to influence these decisions and there should be training, workshops, and seminars regarding potential tea farmers on how they affect the society on agricultural development programs.